Embodied Voices, Disembodied Pages, and the Second-Personal Turn in Aesthetics. Comments on Karen Simecek's Philosophy of Lyric Voice. The Cognitive Value of Page and Performance Poetry. - Clavel-Vázquez, Adriana (Philosophia, 2025)
In Philosophy of Lyric Voice, Karen Simecek develops a second personal approach to the appreciation of poetry. Taking performance poetry as a model, Simecek argues that poetry is inherently relational, that it cannot be reduced to word meaning, and that, therefore, poet-performers' embodiment contributes to the meaning of the works. From this understanding of poetry, the book argues that its cognitive value stems from the opportunities it affords to acknowledge that we engage with one another not just through connection and community, but also through equally valuable tension and friction. While I wholeheartedly agree with Simecek's second-personal proposal, in these comments I develop the worry that the book's account of poetry on the page is inconsistent with its main arguments and commitments.